Hidden Potential of Arak Bali to be The World’s Seventh Spirit; from religious purpose to negative investment list - Putu Herry Hermawan Priantara (Bali Tourism Board, 2019)
In a joint meeting between Governor and Bali Regional House of Representatives on 11 February 2019, Bali Governor Wayan Koster expressed his interest to promote arak as a trademark of Bali, a traditional Balinese spirit. Arak is a type of distilled alcoholic beverage, generally produced in Southeast Asia and South Asia countries. Each region has its distinctive method in selecting the most delicate raw material as primary ingredient, to its patients and meticulous preparations in producing the best liquor. Religious activities becomes chief reason the art of liquor distilation present in the island of God, especially Arak. It serves as tetabuhan in traditional and religious ceremonies, a recreational beverage for adults or even utilize to make herbal paste. Some traditional farmer use Wariga as a reference to determine the perfect day to produce arak, therefore, the process becomes its distinctive feature. Realizing its hidden potential, Governor Koster expressed his interest in making Balinese Arak legal as a prospective industry to improve the communities economic welfare, by promoting it as a heritage-based product. Through departments in Provincial government, he prepares standardisation as well as legal basis to promote the liquor in tourism industry. However, the distilled spirit is classified as Alcohol type C on the law thus its distribution in full scale is strictly regulated by the law. Furthermore, Presidential Regulation which adds alcoholic beverages as negative investment list, become a high wall to climb before the customer could safely sip the product.